The Effect Of Using Question-Answer Relationship (Qar) Strategy On Grade Eleven Students’ Ability In Reading Comprehension Of Narrative Text At Sma Negeri 5 Pematang Siantar - Leli Anggraini; David Berthony Manalu; Partohap Saut Raja Sihombing (Jurnal Ilmu Pendidikan dan Sosial, 2023)
This research aims to see the effect of using the Question-Answer Relationship (QAR) strategy on the ability of eleventh grade students in reading comprehension of narrative texts at SMA Negeri 5 Pematang Siantar. In this study, researchers used a method called quasi-experimental design, which allows researchers to collect numerical data. The population is all class XI students of SMA Negeri 5 Pematang Siantar for the 2023/2024 academic year, totaling 10 classes. The number of students in each class varies, so the total is 360 students. This research sampling involved two classes, namely XI PMIA-1 and XI PMIA-3. Data analysis shows that the experimental class obtained an average post-test score of 86.52, compared to the control class's average score of 80.13. The post-test standard deviation for the experimental class was 6.95, while the control class had a standard deviation of 3.77. Additionally, the standard error of the mean difference was calculated as 3.22. With a significance level of 5%, the T-count value exceeds the T-table value (1.8 > 1.672), so it can be concluded that the T-count is greater than the T-table. This also shows that (Ho) is rejected and (Ha) is accepted.